2021
DOI: 10.1038/s41598-021-98979-6
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and biocatalyst activity of culturable hydrocarbonoclastic fungi isolated from Marac–Moruga mud volcano in South Trinidad

Abstract: Mud volcanoes (MVs) are visible signs of oil and gas reserves present deep beneath land and sea. The Marac MV in Trinidad is the only MV associated with natural hydrocarbon seeps. Petrogenic polyaromatic hydrocarbons (PAHs) in its sediments must undergo biogeochemical cycles of detoxification as they can enter the water table and aquifers threatening ecosystems and biota. Recurrent hydrocarbon seep activity of MVs consolidates the growth of hydrocarbonoclastic fungal communities. Fungi possess advantageous met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 130 publications
1
0
0
Order By: Relevance
“…and Agaricomycetes ( Pleurotus sp.). This distribution aligns with a previous study that sought to identify culturable hydrocarbonoclastic fungus from South Trinidad's Marac-Moruga mud volcano, indicating the highest combined prevalence (89%) within the Dothideomycetes and Eurotiomycetes taxonomic groups 39 . Moreover, we observed that the surface layer (A) contained the highest number of fungi, while the number of isolates decreased in the subsurface levels (B and C).…”
Section: Discussionsupporting
confidence: 89%
“…and Agaricomycetes ( Pleurotus sp.). This distribution aligns with a previous study that sought to identify culturable hydrocarbonoclastic fungus from South Trinidad's Marac-Moruga mud volcano, indicating the highest combined prevalence (89%) within the Dothideomycetes and Eurotiomycetes taxonomic groups 39 . Moreover, we observed that the surface layer (A) contained the highest number of fungi, while the number of isolates decreased in the subsurface levels (B and C).…”
Section: Discussionsupporting
confidence: 89%